Chemical Constituents and Cytotoxic Activity of Silver Comet (Globba Pendula) - Maulidiani, (2007)
In a continuation of our chemical and biological investigations on Zingiberaceae species, we have now studied Globba pendula, a less common ginger plant found in Peninsula Malaysia. This plant has been used traditionally as a protective medicine after childbirth and for treating stomach complaints. No biological activity and chemical constituents have been reported on this species so far. Five of eight extracts including dichloromethane (rhizome and leaf), ethyl acetate (rhizome and leaf), and hexane (leaf) from the sequential extraction of Globba pendula were evaluated for cytotoxic activity. They exhibited cytotoxicity against MCF-7 cells (human breast cancer) with IC50 values ranging from 19.5 to 37.0 μg/ml. The statistical analysis of variance (ANOVA) showed that there were no significant (P<0.05) difference of the cytotoxic activity among the extracts. Phytochemical studies on the rhizomes and leaves of Globba pendula resulted in the isolation of two new compounds. They are 16-oxo-(8)17-12-labdadien-15,11-olide (92) and benzofuran-2-carboxaldehyde (96), along with seven known compounds: 4-hydroxy- 3-methoxybenzoic acid (69), β-sitosterol (73), β-sitosteryl-β-D-glucopyranoside (90), 7α-hydroxysitosterol (91), 3,14,19-trihydroxy-8(17),12-labdadien-16,15-olide (93), 4-hydroxy-3-methoxybenzaldehyde (94), and 2(3H)-benzoxazolone (95). The structures of isolated compounds were established based on spectroscopic data and comparison with the literature. The compound 3,14,19-trihydroxy-8(17),12- labdadien-16,15-olide (94) has demonstrated strong cytotoxic properties towards a panel of cancer cell lines (MCF-7, PC-3, and H-460) with the IC50 values of 7.9, 8.7, and 9.0 μM, respectively.